An Analysis Of Function And Meaning Of “Lega Mitan” Traditional Ceremony In Habi Village - Nona Supartin, Ermelinda; Antonius M. K. Naro; Yanto Yanto (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
This research aims to explain the meaning that can be obtained from the Lega Mitan Traditional Ceremony in Habi Village and identify to the function of the Lega Mitan Traditional Ceremony in Habi Village. The researcher used qualitative method. Data collection techniques used in this research are observation, interview and documentation. The data analysis techniques used by Miles and Huberman in the book Sugiyono (2018) models. In the results there are the function of the Lega Mitan traditional ceremony, especially Habi Village, is as a form of respect for people who have died. The ceremony functions so that the soul of the deceased is more peaceful in the afterlife. The Lega Mitan ceremony is a ceremony that signifies that the grieving period is over. It is called blatan bliran, blatan means cold, bliran means freshness for the two people accompanying the corpse. The values that we can take in carrying out the traditional Lega Mitan ceremony are human values and mutual cooperation.